Gestational Diabetes Mellitus: Prevalence, Management and Prevention - Łakoma, Aleksandra; Choiński, Maciej; Marzec, Weronika Zofia; Wasiewicz-Ciach, Paulina; Marszałek, Anna; Wydra-Rojek, Aleksandra; Kutyła, Katarzyna; Mokot, Wojciech Jan; Marzec, Marcelina Teresa; Kuczyński, Piotr (Quality in Sport, 2024)
Gestational diabetes mellitus (GDM) is a significant health concern for pregnant women, associated with various adverse outcomes for both the mother and the fetus. This systematic review consolidates the current understanding and research on GDM, focusing on its prevalence, prevention, and treatment strategies. The review aims to highlight key findings and areas for future research, emphasizing the need for high-quality, inclusive studies to substantiate the effectiveness of various interventions. The review discusses the pathophysiology of GDM, the impact of maternal and neonatal adverse effects, and the comparison of treatment options such as insulin and metformin. Additionally, the study examines lifestyle interventions, dietary supplementation, and the use of probiotics as preventive measures. Accurate prevalence estimates are essential for the effective allocation of health resources and the development of prevention and management policies to address the rising rates of GDM. This review underscores the importance of standardized diagnostic criteria and screening strategies to obtain accurate and comparable prevalence estimates, ultimately aiming to improve maternal and neonatal health outcomes.